Quasi-solid-state electrolyte for rechargeable high-temperature molten salt iron-air battery - Zhang, Shiyu; Yang, Yun; Cheng, Liwei; Sun, Jian; Wang, Xiaomei; Nan, Pengfei; Xie, Chaomei; Yu, Haisheng; Xia, Yuanhua; Ge, Binghui; Lin, Jun; Zhang, Linjuan; et al. (Elsevier B.V., 2020)
Molten salts are a unique type of electrolyte enabling high-temperature electrochemical energy storage (EES) with unmatched reversible electrode kinetics and high ion-conductivities, and hence impressive storage capacity and power capability. However, their high tendency to evaporate and flow at high temperatures challenges the design and fabrication of the respective EES devices in terms of manufacturing cost and cycling durability. On the other hand, most of these EES devices require lithium-containing molten salts as the electrolyte to enhance performances, which not only increases the cost but also demands a share of the already limited lithium resources. Here we report a novel quasi-solid-state (QSS) electrolyte, consisting of the molten eutectic mixture of Na2CO3-K2CO3 and nanoparticles of yttrium stabilized zirconia (YSZ) in a mass ratio of 1:1. The QSS electrolyte has relatively lower volatility in comparison with the pristine molten Na2CO3-K2CO3 eutectic, and therefore significantly suppresses the evaporation of molten salts, thanks to a strong interaction at the interface between molten salt and YSZ nanoparticles at high temperatures. The QSS electrolyte was used to construct an iron-air battery that performed excellently in charge-discharge cycling with high columbic and energy efficiencies. We also propose and confirm a redox mechanism at the three-phase interlines in the negative electrode. These findings can help establish a simpler and more efficient approach to designing low-cost and high-performance molten salt metal-air batteries with high stability and safety.